P566 Effect of polyethylene glycol (PEG) bowel preparation on faecal calprotectin levels in patients with ulcerative colitis. (16th January 2018) - Herrera-deGuise, C; Varela, E; Robles, V; Casellas, F; Borruel, N
Abstract: Background: Colonoscopy is widely used for diagnosis, evaluation and surveillance in ulcerative colitis (UC). For an adequate evaluation of the colon, patients require a correct bowel preparation. It has been reported that preparation with polyethylene glycol (PEG) can induce inflammation of the colonic mucosa in up to 2% of subjects. Few UC patients have a clinical relapse of the disease after a colonoscopy, although the mechanism is unknown. If bowel preparation can induce mucosal inflammation in healthy subjects, then it could be the trigger for a flare in UC. Faecal calprotectin levels correlate with intestinal inflammation in UC. The aim of this study was to evaluate if PEG oral preparation produces a significant change in calprotectin levels in UC patients and healthy subjects. Methods: Prospective, observational study in UC patients in clinical remission, who required a colonoscopy for surveillance and a group of healthy volunteers. All subjects received an identical PEG bowel preparation. Stool samples were obtained from all subjects 24 h before and after taking PEG. Calprotectin was measured by immunoenzymatic assay. Samples were tested in duplicate and results expressed as μg/g of faeces. Clinical and demographic data of all subjects were collected. Statistical significance was determined with a two-tailed p -value of <0.05. Results: We included 25 subjects in the study, 13 UC patients and 12 healthy volunteers. Mean age was 37.5 ± 11.4 for UC patients and 37.6 ± 13 in controls ( p = ns). The time of evolution of UC was 10.3 ± 7.5 years. Sixty-one percent of UC and 58% of healthy subjects were male ( p = ns). In patients with UC, the average value of calprotectin before and after taking PEG was 120 ± 74 μg/g and 159 ± 82 μg/g, respectively, without finding significant differences ( p = ns). All patients were in endoscopic remission of UC (Mayo score 0 or 1). One patient presented a post-colonoscopy flare of UC that was controlled with oral corticosteroids. In healthy controls, no significant change was observed between the calprotectin value before and after the PEG intake (42.7 ± 17 vs. 47.5 ± 21 μg/g ( p = ns)). Conclusions: PEG bowel preparation does not significantly affect calprotectin levels in UC patients and healthy subjects.